DUKUNG TATA KELOLA KOTA BERKELANJUTAN : AKSI TERTIBKAN KANTONG PARKIR DI PASAR BARU GOTONG ROYONG KOTA PROBOLINGGO - Halima, Nur Halima; Maulidi, Finni; Awaliatul, Wilda (Publicio: Jurnal Ilmiah Politik, Kebijakan dan Sosial, 2021)
In the 21st century, the problem of sustainable development has been used as an important issue that needs to be socialized in the community. in the preparation phase of the action program to regulate parking bags in the new market Gotong Royong Probolinggo City, discussions began from the form of activities, locations, and evaluations. A form of activity that will be carried out by a group of students, which is carried out openly directly on site. The method used in these activities is coordination and communication by plunging directly into the parking lot of The Gotong Royong Market in Probolinggo City with the focus of structuring the parking space in the central Gotong Royong market. With the results of evaluation activities that can be done by students lacking the functioning of parking spaces in the arena gotong royong market and the lack of orderly parking activities in the market, so that it makes the parking arena in the market there are no officers or parking attendants. it is also prone to the loss of vehicles in the market arena. Thus, it can be concluded that parking facilities are used limits to distinguish parking spaces between four wheels and two wheels. This is because the parking system in Gotong Royong market is in accordance with the procedures that have been scheduled and does not cause traffic jams. Keyword : Parking Facilities, Gotong Royong Market, Urban Spatial Planning